2012
DOI: 10.1016/j.sjbs.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Combined inoculation with Glomus intraradices and Rhizobium tropici CIAT899 increases phosphorus use efficiency for symbiotic nitrogen fixation in common bean (Phaseolus vulgaris L.)

Abstract: This study compared the response of common bean (Phaseolus vulgaris L.) to arbuscular mycorrhizal fungi (AMF) and rhizobia strain inoculation. Two common bean genotypes i.e. CocoT and Flamingo varying in their effectiveness for nitrogen fixation were inoculated with Glomus intraradices and Rhizobium tropici CIAT899, and grown for 50 days in soil-sand substrate in glasshouse conditions. Inoculation of common bean plants with the AM fungi resulted in a significant increase in nodulation compared to plants withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 30 publications
3
34
0
5
Order By: Relevance
“…G. constrictum 35-45%, R. intraradices 8-38%). These data show that root colonization was related to numerous interactions between the AMF genotype, soil structure, and also to the interactions between the host plant (Tajini et al 2012). In our work, in spite of the expected low colonization in the sterile substrate, the recorded data showed higher values of the root colonization also for some sterile treatments.…”
Section: Root Colonizationmentioning
confidence: 76%
“…G. constrictum 35-45%, R. intraradices 8-38%). These data show that root colonization was related to numerous interactions between the AMF genotype, soil structure, and also to the interactions between the host plant (Tajini et al 2012). In our work, in spite of the expected low colonization in the sterile substrate, the recorded data showed higher values of the root colonization also for some sterile treatments.…”
Section: Root Colonizationmentioning
confidence: 76%
“…These results were true in the two studied seasons. Accordingly, co-inoculation strategy seemed to be more valuable, with relatively surpassing of mixture treatment comprised (Rhizobium + Serratia + Bacillus + AM-fungi).This could be due to the essential role of Rhizobium in enhancing plant growth and N 2 -fixation, and then it was magnified as a result of co-inoculation with the mixture of PGPRs and/or AM-fungi as reported by (Zaidi et al, 2009;Tajini et al, 2012;Vafadar et al, 2014&Kumar andVerma, 2017). They confirmed that the nitrogen fixers, phosphate-solubilizing fungi and PGPR when inoculated together colonized the rhizosphere and improve plant growth promotion by triggering plant growth hormones, enhance the nutritional capacity of the plants and confer stress tolerance in plants.…”
Section: Plant Growthmentioning
confidence: 89%
“…The promoting effects on nodulation and symbiotic performance might occur through the integration between the various mechanisms offered by mixing more than efficient rhizobacteria and AM-fungi, which act to enhance root proliferation and provide more infection sites to rhizobia. Many investigators confirmed the stimulating effect of PGPR and AM-fungi in creating a favorable habitat for improving nodulation pattern and biological N 2 -fixation (Aysan and Demir, 2009;Badawi et al, 2011;Tajini et al, 2012;Miransari, 2013).…”
Section: Table 3 Nodulation Status Of Faba Bean Plants As Affected Bmentioning
confidence: 94%
See 1 more Smart Citation
“…In turn, tripartite symbiosis (NFB-AMF-legumes) against noninoculated control plant or plant inoculated with AMF or NFB alone, offers benefits to the plant such as enhanced plant growth, crop yield, phosphorus and nitrogen content (Pacovsky et al, 1986;Azcon et al, 1991). In this respect, research studies such as those carried out by Tajini et al (2012) and Abd-Alla et al (2014) showed that dual inoculation improved parameters of nodulation, nitrogenase activity, mycorrhization and nutrients content (N and P) in plant compared with individual inoculation.…”
Section: Introductionmentioning
confidence: 99%